Design and Rationale of the Best Endovascular Versus Best Surgical Therapy for Patients With Critical Limb Ischemia (BEST‐CLI) Trial. Issue 7 (8th July 2016) - Menard, Matthew T.; Farber, Alik; Assmann, Susan F.; Choudhry, Niteesh K.; Conte, Michael S.; Creager, Mark A.; Dake, Michael D.; Jaff, Michael R.; Kaufman, John A.; Powell, Richard J.; Reid, Diane M.; Siami, Flora Sandra; et al.
Abstract : Background: Critical limb ischemia (CLI) is increasing in prevalence, and remains a significant source of mortality and limb loss. The decision to recommend surgical or endovascular revascularization for patients who are candidates for both varies significantly among providers and is driven more by individual preference than scientific evidence. Methods and Results: The Best Endovascular Versus Best Surgical Therapy for Patients With Critical Limb Ischemia (BEST‐CLI) Trial is a prospective, randomized, multidisciplinary, controlled, superiority trial designed to compare treatment efficacy, functional outcomes, quality of life, and cost in patients undergoing best endovascular or best open surgical revascularization. Approximately 140 clinical sites in the United States and Canada will enroll 2100 patients with CLI who are candidates for both treatment options. A pragmatic trial design requires consensus on patient eligibility by at least 2 investigators, but leaves the choice of specific procedural strategy within the assigned revascularization approach to the individual treating investigator. Patients with suitable single‐segment of saphenous vein available for potential bypass will be randomized within Cohort 1 (n=1620), while patients without will be randomized within Cohort 2 (n=480). The primary efficacy end point of the trial is Major Adverse Limb Event–Free Survival. Key secondary end points include Re‐intervention and Amputation‐Free‐Survival and Amputation Free‐Survival. Conclusions: The BEST‐CLI trial is the first randomized controlled trial comparing endovascular therapy to open surgical bypass in patients with CLI to be carried out in North America. This landmark comparative effectiveness trial aims to provide Level I data to clarify the appropriate role for both treatment strategies and help define an evidence‐based standard of care for this challenging patient population. Clinical Trial Registration: URL:https://www.clinicaltrials.gov/ . Unique identifier: NCT02060630.